Investigation of Water Quality Parameters Discharged from Textile Dyeing Industries - Munnaf, A; Islam, MS; Tusher, TR; Kabir, MH; Molla, MAH (Journal of Environmental Science and Natural Resources, 2015)
Rapid development of textile industry and direct deposition of the effluents into sewage networks produced disturbances in treatment processes and exert pollution loads on water bodies. The study was conducted to investigate the water quality parameters discharged from seven textile dyeing industries at Konabari in Gazipur region of Bangladesh during March to December, 2011, and also to evaluate the harmful effects of effluents on the surrounding environment. Emphasis was given on the investigation of important water quality parameters, which include temperature, pH, total suspended solids (TSS), total dissolved solids (TDS), dissolved oxygen (DO), biochemical oxygen demand (BOD) and chemical oxygen demand (COD), along with the management techniques of effluents discharged from textile dyeing industries. The study depicted that the DO values were nil or below the standard values in all industries which was very alarming for environment. The concentrations of BOD, COD, TDS and TSS were very high which indicate the presence of water pollutants. The study was focused on the pollution implications of effluents from textile industries around the study area, because of the risk of human exposure and environmental degradation by these massive discharged effluents. The water quality deteriorated in dry season than the wet season and the surface water around the studied area was highly polluted due to the industrial activities and should totally avoid for human consumption without proper treatment. It is therefore recommended that the careless discharge of the effluents should be discouraged and appropriate management system should be taken immediately to reduce the water pollution for saving the environment. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22180 J. Environ. Sci. & Natural Resources, 7(1): 257-263 2014